Tradisi Doa Akasyah Masyarakat Melayu: Studi Living Hadis di Kabupaten Ketapang Kalimantan - Samanarnik (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2023)
This research examines a tradition within the Malay community, particularly in Ketapang Regency, West Kalimantan, and its surrounding areas. The research employs a field research method, utilizing a phenomenological approach. This study focuses on discussing the significance of the Akasah Prayer within the Ketapang community. The research reveals that the tradition of the Akasah Prayer manifests the application of living hadith by the community. Within this tradition, cultural values are integrated with religious teachings. These values include practices that were once performed with offerings to supernatural beings believed to be ancestors to attain prosperity and ward off various illnesses. Subsequently, these practices have been adapted to religious values by incorporating prayers as a form of supplication to God.